Chemical Durability of Lanthanum‐Enriched Borosilicate Glass. (9th November 2013) - Molières, Estelle; Angeli, Frédéric; Jollivet, Patrick; Gin, Stephane; Charpentier, Thibault; Majérus, Odile; Barboux, Philippe; de, Dominique; Spalla, Olivier
<x xml:space="preserve">Abstract</x> The role of lanthanum in the alteration kinetics at different degrees of reaction progress was investigated at 90°C and pH 7 by complementary chemical (SIMS), morphological (SAXS), and structural (NMR, Raman, and EXAFS spectroscopy) approaches. In the first step of alteration, the forward dissolution rate diminishes with the addition of lanthanum, resembling to the behavior previously observed for zirconium. Over longer alteration time, the glasses with the highest lanthanum concentrations reach silicon saturation more slowly, but unlike zirconium, do not result in larger quantities of altered glass. Lanthanum is entirely retained in the alteration layer and is uniformly distributed; it undergoes hydrolysis and recondensation mechanisms, and its coordination number increases from 6 to 9 during leaching. Reconstruction of the alteration layer occurred more slowly at higher REE concentrations, with a slowdown in repolymerization of the silicate network and structuring of its porosity.